2021
DOI: 10.1016/j.jebo.2021.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Socially optimal mistakes? debiasing COVID-19 mortality risk perceptions and prosocial behavior

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 91 publications
4
39
0
Order By: Relevance
“…Our findings also suggest that altruism is the predominant reason to give in the context of immunization against a pandemic, reported by a majority of respondents who would donate to nongovernmental immunization campaigns. This is consistent with recent studies that found that prosocial attitudes are related to WTG amid the COVID-19 pandemic (Abel et al, 2021;Campos-Mercade et al, 2021). Impure altruism in the form of benefiting from a public good was the second most popular motive, as reported by almost 29% of those who would give.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings also suggest that altruism is the predominant reason to give in the context of immunization against a pandemic, reported by a majority of respondents who would donate to nongovernmental immunization campaigns. This is consistent with recent studies that found that prosocial attitudes are related to WTG amid the COVID-19 pandemic (Abel et al, 2021;Campos-Mercade et al, 2021). Impure altruism in the form of benefiting from a public good was the second most popular motive, as reported by almost 29% of those who would give.…”
Section: Discussionsupporting
confidence: 91%
“…Campos-Mercade et al (2021) found that more than 20% of respondents would not donate to the proposed fund, almost 50% would donate half of the value of the gift card, and the rest would donate something in between. 1 In a similar study, Abel et al (2021) implemented online experiments to measure perceived risks of COVID-19. After a series of experiments, participants were offered a bonus of $0.50 for completing the survey.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Young people's vaccine intentions are higher than the general population (Benis et al, 2021). Previous research suggested that women, lower-income and lower education individuals in developed countries would seek to mitigate health risks by vaccination (Dohmen et al, 2021) due to higher perceived infection health risks (Abel et al, 2021). Educated people in developed countries may have low intention to adopt vaccination, due to perceived vaccine side effects and lower perceived infection risks (Larson et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%